2006
DOI: 10.1002/art.22161
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M induces angiogenesis and cartilage degradation in rheumatoid arthritis synovial tissue and human cartilage cocultures

Abstract: Conclusion. These data suggest that OSM promotes angiogenesis and endothelial cell migration and potentiates the effects of IL-1␤ in promoting extracellular matrix turnover and human cartilage degradation. Furthermore, the induction of VEGF in cocultures supports the hypothesis of a link between angiogenesis and cartilage degradation.Rheumatoid arthritis (RA) is a chronic disease characterized by synovial tissue proliferation and articular cartilage degradation (1,2). In RA, angiogenesis is an early event requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
85
1
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 49 publications
3
85
1
1
Order By: Relevance
“…So far, most studies corroborating the involvement of OSM in the development and progression of RA have highlighted its contribution to cartilage breakdown preferentially by up-regulation of MMPs and aggrecanases (18,20,22,26,46) as well as changes in the MMP:TIMP ratio in favor of MMPs (19,37). In this study, we identified OSM as the main regulator of CCL13 chemokine expression by SFs.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…So far, most studies corroborating the involvement of OSM in the development and progression of RA have highlighted its contribution to cartilage breakdown preferentially by up-regulation of MMPs and aggrecanases (18,20,22,26,46) as well as changes in the MMP:TIMP ratio in favor of MMPs (19,37). In this study, we identified OSM as the main regulator of CCL13 chemokine expression by SFs.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, the relevance of OSM in arthritis was shown in a murine model in which application of antibodies to OSM ameliorated arthritis (17). The impact of OSM on remodeling the joint architecture and therefore on the course of RA is reflected by the release of proteoglycan and collagen from local cartilage, the triggered expression of angiogenic factors such as vascular endothelial growth factor and fibroblast growth factor, as well as the stimulation of synovial fibroblast (SF) proliferation (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…24,25 In chondrocytes, OSM induces aggrecanases and collagenases such as MMP-1, MMP-3 and MMP-13, leading to extensive cartilage breakdown. 18,22 On RA synovial fibroblasts co-cultured with cartilage explants, OSM also enhances VEGF production. 18 OSM is known to induce VEGF expression in various cancer cell types through activation of STAT3 26 and to increase endothelial cell tubule formation.…”
mentioning
confidence: 98%
“…13,14 Oncostatin M (OSM) is a pro-inflammatory cytokine of the IL-6 family which is composed of nine members such as IL-27 and leukemia inhibitory factor (LIF). 15 OSM has cytostatic activities on sarcoma and carcinoma cell lines, [15][16][17] activates endothelial cells, 18 induces acute phase proteins production by liver as well as inflammatory and immune responses in various tissues such as skin, lung and bone/cartilage. 15,19,20 In human, this pleiotropic cytokine can bind to the type I heterodimeric receptor composed of gp130 and LIF receptor (LIFR) 21 or to the type II receptor composed of gp130 and OSMR.…”
mentioning
confidence: 99%
See 1 more Smart Citation